Pelaksanaan Perjanjian Sewa Beli Kendaraan Bermotor Akibat Overmacht Karena Covjd-19 di PT. Federal International Finance(FIF) Kabupaten Karangasem - Anak Agung Ayu Agung Cleo Bayu Pertiwi; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2021)
The financial sector in Indonesia is a sector that is most important than advancing and developing the level of the economy. This of course needs to be maintained both by banks and other financial institutions so that the process of economic development in Indonesia is not delayed. Moreover to maintain this thing, it is necessary to make improvements which in particular do it with financial institutions and of course not banks. The purpose of this study is to reveal the factors that cause overmacht due to Covid-19 at PT. Federal International Finance (FIF) Karangasem Regency and efforts to resolve the overmacht due to Covid-19 at PT. Federal International Finance (FIF) Karangasem Regency. This research method using empirical legal research with a literature study approach. The sources of data used are primary data and secondary data. Data collection techniques by observing, interviewing and documentation methods. After primary legal data and secondary legal data are collected, the data will then be processed and analyzed using systematic legal data processing methods. The research results reveal that some of the problems identified lie in internal and external factors where these problems cannot be borne by the consumer and beyond the control of the consumer himself. The overmatch settlement is carried out by using non-litigation.